Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/nature14664
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic profiles of small cell lung cancer

Abstract: We have sequenced the genomes of 110 small cell lung cancers (SCLC), one of the deadliest human cancers. In nearly all the tumours analysed we found bi-allelic inactivation of TP53 and RB1, sometimes by complex genomic rearrangements. Two tumours with wild-type RB1 had evidence of chromothripsis leading to overexpression of cyclin D1 (encoded by the CCND1 gene), revealing an alternative mechanism of Rb1 deregulation. Thus, loss of the tumour suppressors TP53 and RB1 is obligatory in SCLC. We discovered somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

121
2,352
10
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,786 publications
(2,491 citation statements)
references
References 46 publications
(95 reference statements)
121
2,352
10
8
Order By: Relevance
“…Changes that activate differentiation programs are one potential strategy (MacLellan et al 2000;Lasorella et al 2005;Lin et al 2011). Recent work has suggested that Notch signaling may be important in mouse models of small-cell lung cancer, one of the most common types of RB1 mutant cancers (George et al 2015). Inactivation of Sox2 has also been shown to suppress RB1 mutant pituitary tumors in mouse models (Kareta et al 2015).…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%
“…Changes that activate differentiation programs are one potential strategy (MacLellan et al 2000;Lasorella et al 2005;Lin et al 2011). Recent work has suggested that Notch signaling may be important in mouse models of small-cell lung cancer, one of the most common types of RB1 mutant cancers (George et al 2015). Inactivation of Sox2 has also been shown to suppress RB1 mutant pituitary tumors in mouse models (Kareta et al 2015).…”
Section: The Translation Of Rb Researchmentioning
confidence: 99%
“…FGFR1 amplification was also observed in small-cell lung cancer-one of the most deadly malignancies (6% of cases; refs. 7,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…13). Three landmark studies comprehensively characterized the SCLC genomic landscape, identifying alterations in genes encoding histone modifying proteins and transcription factors, including SOX2 and NOTCH family genes (10,14,15). These studies revealed a mutation rate of 5.5 to 8.6 coding mutations per Mb (10,14,15).…”
Section: Introductionmentioning
confidence: 99%